Faktor-faktor Penentu Keberhasilan Inovasi Dalam Penyelenggaraan Pemerintah Daerah - Aminah, Sitti (Jurnal Wahana Bina Pemerintahan, 2016)
The aims of the study was to describe innovations in local goverment and the factor that determines success of innovation in local governance. Qualitative approach is used to answer the questions proposed in this study. The result of this study shows that the complexity of the problems in goverment requires innovation in handling by the local goverment. Factors that determine the success of innovation in local goverment were readiness of policies and regulations, innovative leadership, culture of innovation, readiness to coordinate and facilitate, the role of stakeholder and readiness of infrastructure.